2019
DOI: 10.1155/2019/4609353
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Incorporation of Marble Powder Obtained by Recycling Waste Sludge and Limestone Powder on Rheology, Compressive Strength, and Durability of Self-Compacting Concrete

Abstract: Marble has been commonly used as a building material since ancient times. e disposal of waste materials from the marble industry, consisting of sludge that is composed of powder mixed with water, is one of the current worldwide environmental problems. is experimental study aims to valorize marble powder, which is achieved by grinding the sludge as filler added to the cementitious matrix of self-compacting concrete (SCC). e main purpose of this work is to evaluate the marble filler effects on the rheology in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 36 publications
3
17
0
Order By: Relevance
“…The summary of the values of the percentage voids, voids in mineral aggregates, and voids filled with bitumen are given in Table 7 and the plot of the relationship between the binder content and these variables for each addition of WMD are given in Figure 5. The voids percentage allowed for asphalt concrete mixes is in the range of 5 -10% [30]. From Figure 6a, the voids for the neat sample are above 10% for the different binder percentages.…”
Section: Effects Of Wmd On the Marshall Flowmentioning
confidence: 93%
See 1 more Smart Citation
“…The summary of the values of the percentage voids, voids in mineral aggregates, and voids filled with bitumen are given in Table 7 and the plot of the relationship between the binder content and these variables for each addition of WMD are given in Figure 5. The voids percentage allowed for asphalt concrete mixes is in the range of 5 -10% [30]. From Figure 6a, the voids for the neat sample are above 10% for the different binder percentages.…”
Section: Effects Of Wmd On the Marshall Flowmentioning
confidence: 93%
“…Asphalt concrete with lower values of Marshall flow tends to fail due to disintegration, while higher values mean that the workability is also greatly reduced if they exceed the given limits. As per the specification, the Marshall flow should range between 2 and 4mm [30]. The Marshall Flow values obtained from this study's samples are as tabulated in Table 6.…”
Section: Effects Of Wmd On the Marshall Flowmentioning
confidence: 99%
“…In this case, mixtures with sulfur have lower compressive strength. Similarly to the use of porous aggregates, such as recycled concrete aggregate (73), difference in porosity of the used filler directly affects the water volume available for the chemical reactions, i.e., lower the porosity of filler, higher the 'free' water content, and, consequently, the higher effective water to cement ratio, and finally lower compressive strength (74).…”
Section: Compressive Strengthmentioning
confidence: 99%
“…A study reported that the elastic modulus, creep and shrinkage of SCC did not differ significantly from the corresponding properties of normal strength concrete (NSC) [43]. Some of the durability tests, including chloride penetration, water permeability and absorption, gas permeability, carbonation, electrical resistivity, sulfate attack, acid attack, frost resistance, and scaling, have been investigated [17,19,23,44] and more especially the fire resistance, cooling methods, weight loss, and residual mechanical properties of SCC [5,[45][46][47]. Only few studies were found in the literature that investigated HPSCC [2,9,48,49] and its optimization [50][51][52]; these studies had focused on mechanical properties with either porosity, workability, water penetration, rheological properties, exposure to elevated temperature, or one durability test; but frost or scaling resistance of SCC have rarely been investigated in the literature.…”
Section: Introductionmentioning
confidence: 99%